Energy in the 21st century - Fanchi, John R.; Fanchi, Christopher J. (World Scientific, 2017)
The cost and availability of energy significantly impacts our quality of life, the health of national economies, the relationships between nations, and the stability of our environment. What kind of energy do we want to use in our future? Will there be enough? What will the consequences of our decisions be? This book delves into the most prominent energy issues of our time.